Does Board Composition Influence CSR Disclosure? Evidence from Dynamic Panel Analysis - Dang, Rey; Houanti, L’Hocine; Lê, Nhu-Tuyen; Sahut, Jean-Michel (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Given the importance of corporate social responsibility (CSR) and corporate governance, this study examines the association between board composition and CSR disclosure on a sample of S&P 500 firms over the period from 2004 to 2015. Unlike existing studies, we control for potential sources of endogeneity using a system-generalized method of moments (system GMM) estimator. In doing so, we find no evidence that board size, board independence or CEO duality has any significant influence on CSR disclosure. Rather, our results suggest that, when the problem of endogeneity is correctly taken into account, the link between board composition and CSR disclosure is neutral.